1942
DOI: 10.1172/jci101325
|View full text |Cite
|
Sign up to set email alerts
|

The Relation of the Serum Antistreptolysin Titer to the Exacerbation in Chronic Glomerulonephritis

Abstract: In the present study, the relation of the serum antistreptolysin titer to the exacerbation in chronic glomerulonephritis has been analysed. In a previous study (1), an exacerbation in chronic glomerulonephritis was defined arbitrarily as an abrupt and marked increase in the degree of hematuria. It was pointed out that slight variations in the urinary output of erythrocytes perhaps do not signify the presence of an exacerbation. Exacerbations were frequently associated with some impairment of renal function, ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1942
1942
1959
1959

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The relation of the serum antistreptolysin titer response to the exacerbation in chronic glomerulonephritis is discussed in the accompanying paper (10).…”
Section: Summary Of Materialsmentioning
confidence: 99%
“…The relation of the serum antistreptolysin titer response to the exacerbation in chronic glomerulonephritis is discussed in the accompanying paper (10).…”
Section: Summary Of Materialsmentioning
confidence: 99%
“…In rheumatic fever the latent period remained constant in each exacerbation. Subsequently, Earle, Seegal, Lyttle, Loeb, and Jost (20) showed that in contrast to rheumatic fever the exacerbation in seven of eight cases of nephritis was fully developed before the antistreptolysin titer increased. Recently Fischel and Gajdusek (21) observed a serological difference between nephritis and rheumatic fever.…”
Section: Introductionmentioning
confidence: 99%